Self-assembly of cyclometallated Pd(II) compounds directed by C-H center dot center dot center dot pi interactions: A structural evidence for metalloaromaticity in a cyclopalladated ring - Santana, Anderson M. [UNESP]; Ferreira, Janaina G. [UNESP]; Moro, Antonio C. [UNESP]; Lemos, Sahra C. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Frem, Regina Célia Galvão [UNESP]; Santos, Regina H. A. (Elsevier B.V., 2011)
Structural studies on the two binuclear cyclometallated compounds [Pd(C-2,N-bzan)(mu-N-3)](2) (1) and [Pd(C-2,N-bzan)(mu-Pz)](2) (2) (bzan = N-benzylideneaniline) have been carried out in this work. In both compounds, C-H center dot center dot center dot pi interactions play an important role in the molecular self-assembly. In complex 1, ortho-CH bonds from bzan moiety interact with the cyclopalladated ring at a distance of C-bzan center dot center dot center dot C-g 3.448(6) angstrom, providing a new structural evidence for the metalloaromaticity of the cyclometallated ring. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Supramolecular chemistry; C-H center dot center dot center dot pi interactions; Cyclopalladated; Metalloaromaticity